The Use of Agricultural Unmanned Aerial Vehicles in the Russian Federation: Assessment of Consumer Preferences - Urasova, A. A.; Glezman, L. V.; Fedoseeva, S. S. (Ekonomika regiona, 2023)
In the context of implementing import substitution policy and achieving technological sovereignty, the Russian Federation strives to accelerate the implementation of new technologies in agricultural production. The article assesses regional consumer preferences in the market of agricultural unmanned aerial vehicles (UAVs) using the example of ultra-low-volume spraying technology. It is hypothesised that consumer preferences in this market are affected by natural and climatic factors, including cultivated land size, climatic conditions and terrain diversity. To perform parsing analysis, a script in the Python programming language was created, which receives information about the number of search queries characterising the popularity of agricultural UAVs. The article presents the results of queries from February 2021 to June 2022, taking into account the seasonal nature of agricultural activities. Data on the frequency of queries, including more than 500 measurements from more than 380,000 indicators, were processed using the Yandex. Wordstat service. “Agrodrone” and “agricultural spraying drone” are the most frequently searched queries in Moscow city, Moscow oblast and Krasnodar krai. Moscow and Moscow oblast are characterised by the central location and high concentration of financial and technological resources, while Krasnodar krai is known for large cultivated land areas and favourable climatic conditions for crop production. UVAs are also popular in such mountainous regions as the Republic of North Ossetia-Alania and the Republic of Adygea, since they can be used for crop treatment instead of high-cost self-propelled sprayers and small aircraft. Therefore, the study confirmed a correlation between regional popularity of agricultural UVAs and regional characteristics of agricultural organisation in Russia. Further research can assess the implementation of individual technologies using agricultural UAVs to develop strategic priorities for ensuring food security and achieving technological sovereignty of Russian regions.